Stress-induced hyperlocomotion as a confounding factor in anxiety and depression models in mice - Strekalova, Tatyana; Spanagel, Rainer; Dolgov, O.; Bartsch, Dusan (Behavioural pharmacology, 2005)
Chronic stress is broadly used to model anxiety and depression. However, in chronic stress models, anxiety- and depression-like behaviors might be masked by unspecific effects of stress. We tested whether chronic stress in mice can induce unspecific changes in locomotion, and whether these changes interfere with the measurement of anxiety and forced-swimming behaviors. Also, we studied these latter behaviors in relation to the duration of stress, the lighting conditions during testing, and after the injection of diazepam. We employed a 4-week chronic stress paradigm, adopted from a model of stress-induced anhedonia and a 1-week subchronic stress, both consisting of rat exposure, restraint stress and tail suspension. Chronically stressed mice, tested under bright and moderate illumination, exhibited ‘anxiolytic-like’ behavior along with prolonged swimming and hyperactivity. These behaviors were not detectable under weak illumination or after the injection of diazepam (0.25 mg/kg). Instead, normal locomotion, increased anxiety and inhibited swimming were revealed under these conditions. Thus, chronic stress can induce hyperlocomotion in mice, which is triggered by acute stressors such as light, and interferes with the evaluation of anxiety and forced swimming. One week of stress did not change locomotion and forced swimming, and increased anxiety irrespective of illumination applied during testing. Our data can possibly explain previously reported contradictions in the behavioral testing of mice with chronic stress models of anxiety and depression.